Biochar-based thin-layer capping of contaminated sediment in Burefjärden, northern Sweden : Assessment of biochar mixed into four structural materials for preventing release of trace elements from sediment to water - Pantzare, Nathalie (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
Coastal areas around the world have been recognized as largely impacted by anthropogenic activities resulting in pollution of marine sediments. In Sweden, surveys conducted along the coastline of the Bothnian Bay have identified a total area of about 29 km2 as fiber rich sediments. In the Bureå sea area near Skellefteå vicinity, Västerbotten county, elevated levels of mercury (Hg), methyl-Hg, arsenic (As), copper (Cu), lead (Pb), cadmium (Cd), zinc (Zn) and polycyclic aromatic hydrocarbons (PAH) have been classified and believed to be mainly affected by emissions from a pulp and paper industry formerly active on a nearby headland. Contaminants in sediments are of concern as continuous dispersion can adversely affect the benthic community. To isolate contaminants and reduce their bioavailability, in-situ thin-layer capping using an active material is one suitable approach. This type of remediation method, using biochar mixed with bentonite clay will be implemented on a pilot scale in the sea area outside of Bureå in the spring of 2021. However, bentonite is a relatively expensive material yielding a need to further develop the selection of capping materials suitable to aid in the deposition of biochar in an active thin-layer cap. In this thesis, biochar-based thin layer caps mixed with bentonite clay, rock dust of two grain sizes and a concrete-based slurry was evaluated on their physicochemical properties and efficiency for preventing release of trace elements from sediment to the overlying water. This was conducted by a laboratory column experiment where four set ups were performed: (1) no capping for sediment control, (2) only capping material for material control, (3) sediment mixed with biochar and (4) sediment capped with each material mixed with biochar. Three times during an 8-week test period, 60 mL of the overlying water in the columns was extracted and sent for trace element analysis. The experimental set up revealed that the capping layers effectively prevent release of trace elements trough the ...